MicroRNA-155 Controls iNKT Cell Development and Lineage Differentiation by Coordinating Multiple Regulating Pathways - Wang, Jie; Li, Kai; Zhang, Xilin; Li, Guihua; Liu, Tingting; Wu, Xiaojun; Brown, Stephen L.; Zhou, Li; Mi, Qing-Sheng (Frontiers in Cell and Developmental Biology, 2021)
The development of invariant natural killer T (iNKT) cells requires a well-attuned set of transcription factors, but how these factors are regulated and coordinated remains poorly understood. MicroRNA-155 (miR-155) is a key regulator of numerous cellular processes that affects cell development and homeostasis. Here, we found that the miR-155 was highly expressed in early iNKT cells upon thymic section, and then its expression is gradually downregulated during iNKT cell development. However, the mice with miR-155 germline deletion had normal iNKT cell development. To address if downregulated miR-155 is required for iNKT cell development, we made a CD4Cre.miR-155 knock-in (KI) mouse model with miR-155 conditional overexpression in the T cell lineage. Upregulated miR-155 led to interruption of iNKT cell development, diminished iNKT17 and iNKT1 cells, augmented iNKT2 cells, and these defects were cell-intrinsic. Furthermore, defective iNKT cells in miR-155KI mice resulted in the secondary innate-like CD8 T cell development. Mechanistically, miR-155 modulated multiple targets and signaling pathways to fine tune iNKT cell development. MiR-155 modulated Jarid2, a critical component of a histone modification complex, and Tab2, the upstream activation kinase complex component of NF-B, which function additively in iNKT development and in promoting balanced iNKT1/iNKT2 differentiation. In addition, miR-155 also targeted Rictor, a signature component of mTORC2 that controls iNKT17 differentiation. Taken together, our results indicate that miR-155 serves as a key epigenetic regulator, coordinating multiple signaling pathways and transcriptional programs to precisely regulate iNKT cell development and functional lineage, as well as secondary innate CD8 T cell development.